Surface modification of recycled low-density polyethylene for separation of emulsified oily polluted waters - Sarah M. Hailan (22330417) (2025)
This study addresses two key environmental challenges in the petrochemical industry: the purification of oil-contaminated industrial wastewater from upstream operations, such as drilling, extraction, and crude oil processing, and the efficient utilization of polymeric waste. The work focuses on removing crude oil from kinetically stable oil-in-water (o/w) emulsions with the assistance of appropriately modified recycled low-density polyethylene (LDPE) waste. Because the oily droplets are small in size (less than 1 μm), these emulsions pose a challenge for purifying oily, polluted industrial waters, such as produced water, using traditional sorbents in mainly deep-bed filtration setups. This study presents a novel adsorbent composed of powdered LDPE coated with a specific polymeric layer that exhibits affinity for negatively charged oil droplets. This polymer is synthesized by radiofrequency plasma polymerization of allylamine directly on the surface of LDPE powder. Separation tests were conducted on emulsions with varying compositions and acidity using both batch and filtration modes. At pH = 3, the newly developed sorbent achieved approximately 60% separation efficiency for emulsions containing 100 ppm of oil with droplet sizes below 1 μm. Kinetic analysis showed a strong relationship between the experimental data and the Elovich model. This study highlights the potential of a cost-effective, easily prepared adsorbent derived from LDPE recyclates for purifying emulsified, oil-contaminated water. Other Information Published in: Emergent Materials License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s42247-025-01234-1